Pembelajaran Interaktif dan Media Audio-Visual: Kunci Peningkatan Pemahaman Siswa SMP - Sanuardi, Sanuardi; Nahdi, Khirjan; Murcahyanto, Hary (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the effect of audio-visual media and interactive learning on student motivation and comprehension in learning Indonesian descriptive text at SMP Negeri 5 Jerowaru. The method used was a mixed-method approach with a quasi-experimental design and ANOVA. The results showed that audio-visual media and interactive learning significantly increased student motivation and comprehension. The experimental group, which employed both methods, demonstrated higher motivation and learning outcomes than the control group, which used the lecture method alone. In conclusion, audio-visual media and interactive learning can improve student motivation and learning outcomes. Keywords: Audio-Visual Media, Learning Motivation, Interactive Learning, Descriptive Text